Geospatial Assessment of Water Suitability for Rabbitfish (Siganus sp.) Cultivation in Moyohilir Waters, West Nusa Tenggara - Sarjito Sarjito; Beta Ali Syahbana; Muhammad Helmi; Anindya Wira Satriya; Parichat Wetchayont; Restiana Wisnu Ariyati (Marine Science Department Diponegoro University, 2025)
Rabbitfish (Siganus sp.) is an economically valuable fishery commodity widely consumed in eastern Indonesia, with increasing demand for animal protein. Indonesia’s rabbitfish production rose steadily from 13.6 million tons in 2011 to 22.6 million tons in 2016 but declined after 2017, reaching 21.8 million tons in 2021. Most of this production came from capture fisheries, with only a small portion from the aquaculture sector. To address the declining production, sustainable farming development is essential to improve the stability of rabbitfish supply. The waters of Moyohilir, Sumbawa Regency, exhibit strong potential for rabbitfish cultivation. However, a comprehensive site suitability assessment is essential before initiating aquaculture activities. This study utilized Geographic Information Systems (GIS) to analyze spatial suitability for floating net cage systems. Primary water quality data, namely temperature, salinity, pH, dissolved oxygen, brightness, nitrate, phosphate, and seabed type, were collected from 40 purposively selected sampling points. Secondary data on current speed and water depth were obtained from 2023 bathymetric and wind speed datasets. All parameters were analyzed geospatially using ArcGIS version 10.8. The results revealed three suitability classes: Less Suitable (39.98%; 479.86 ha), Moderately Suitable (48.38%; 595.4 ha), and Suitable (12.64%; 155.57 ha). Based on this assessment, 10% of the Moderately Suitable and Suitable areas, equivalent to 75.1 ha, are recommended for cultivation. This area has the potential to produce up to 117.55 tons of rabbitfish per cycle, supported by 830 floating net cage units, assuming a 60% survival rate.